Tensile Strength of Epoxy Hybrid Composites Reinforced with Coconut and Sugarcane Fibers - Siregar, Muhammad Yasin; Fathar Fathan Mubin; Wahyu Solafide Sipahutar; Anisa Fitri; Mochamad Ghulam Isaq Khan (Universitas Nusa Putra, 2025)
The use of hybrid composites reinforced with natural fibers has gained increasing attention as a sustainable alternative to synthetic materials, offering advantages in both environmental impact and mechanical performance. This study explores the tensile properties of epoxy-based hybrid composites reinforced with coconut and sugarcane fibers at various volume fractions. The natural fibers were pretreated using a 5% NaOH alkaline solution to enhance interfacial bonding with the matrix. Composite specimens were fabricated by the hand lay-up method, maintaining a total fiber content of 50% and an epoxy matrix of 50%, with varying ratios of coconut to sugarcane fiber. Tensile tests were performed according to ASTM D3039 standards. The results showed that alkali treatment improved fiber wettability, as indicated by a decrease in contact angle, which contributed to stronger fiber-matrix adhesion. The highest ultimate tensile strength (31.02 MPa) was achieved at a 30:20 coconut-to-sugarcane fiber ratio. Hybrid composites with balanced fiber proportions demonstrated superior tensile performance compared to single-fiber composites. These findings indicate that optimizing the ratio of coconut and sugarcane fibers can significantly enhance the mechanical properties of natural fiber-reinforced epoxy composites for engineering applications